X-Ray Crystallographic Studies Of Systemic Fungicide Dimethomorph - DR JYOTSNA CHAUHAN; RAJESH KUMAR (International Journal of Pharma and Bio Sciences, 2011)
There are large numbers of chemical compounds for the protection of crops available commercially in the market but their effects depends on the climate, type of soil, and other physical parameters. The interactions of proposed fungicides with the macromolecule of the parasite are dependent on the stereochemistry of these compounds. In order to design more effective synthetic fungicides, it is necessary to analyze the three dimensional structure of these compounds and if possible the receptor molecule. Recently it has been observed that some of the fungicides are loosing their effects. if their structures are known we can design analogous compounds as a substitute. A rational approach to test these fungicides is to know the three dimensional structure of these compounds and macromolecular receptor sites as well as their molecular complex .The structures of these compounds can be obtained by X-ray diffraction method in crystalline form and they will invariably be similar to their structure in solutions. The composition of crystal Dimethomorph is confirmed by comparing the infra-red spectra of two components. The unit cell parameters are a=8.593(5) Å, b=11.220(5)Å, c=11.712 (5) Å, a=63.50 (5)o, b=72.17 (5)o, g=85.39(5)o. The Crystal system is Triclinic and space group is P-1